Offending Heaven and Earth: Sin and Expiation in Islamic Homicide Law - Powers, Paul (Islamic law and society, 2007)
Abstract The Qur'ān clearly condemns homicide and assigns the freeing of a slave to any who kill accidentally. Classical fiqh manuals, however, display a remarkable range of responses to and disagreements about this dictate. Many jurists hold that freeing a slave here is an instance of kaffāra (expiation), understood as an antidote to sin. Yet accidental homicide is widely deemed non-sinful, so kaffāra is assigned for a non-sin. Further, many say the sin of intentional homicide cannot be expiated. Hanafīs often add the idiosyncratic assertion that freeing a slave is not kaffāra but rather an instance of "thanking the benefactor," an altogether different kind of act. I conclude that freeing a slave in response to homicide is not consistently treated as the expiation of sin. Further, the jurists' treatment of kaffāra forces a reconsideration of the commonplace assertion that Islamic law treats murder as more tort than crime.